Estradiol Treatment during Perinatal Development Alters Adult Partner Preference, Mating Behavior and Estrogen Receptors α and β in the Female Mandarin Vole (Microtus mandarinus) - He, Feng-Qin (Zool Stud, 2019)
During development, many aspects of behavior, including partner preferences and sexual conduct, are “organized” by estradiol. This study aimed at analyze these processes in the mandarin vole (Microtus mandarinus), a novel experimental mammal with strong monogamous pair bonds. Female pups were treated daily with an oil vehicle (FC) or β-Estradiol (E(2), FT) from prenatal day 14 to postnatal day 10. Male pups were treated daily with the oil vehicle only (MC). Partner preferences, sexual conduct and the expression of estrogen receptors α (ERα) and β (ERβ) were examined when animals were 3 months old. FT and MC groups showed female-directed partner preferences and masculinized behavior. ERα-immunoreactive neurons (ERα-IRs) in the bed nucleus of stria terminalis (BNST) and medial amygdaloid nucleus (MeA) was greater in FT females than MC males, and there was no significant difference in the number of ERα-IRs between FT and FC females. No difference was found for ERα-IRs in the preoptic area (mPOA) or ventromedial nucleus of the hypothalamus (VMH) of FT females or MC males, and they were significantly fewer than in FC females. ERβ-immunoreactive neurons (ERβ-IRs) in these four brain regions did not alter the ERβ/ERα ratio in different brain regions during perintal developments. However, the number of ERβ-IRs in FT females and MC males were greater than in FC females. We propose that estradiol treatment during perinatal development is responsible for adult partner preferences and mating behavior.